2018
DOI: 10.48084/etasr.2342
|View full text |Cite
|
Sign up to set email alerts
|

RSW Junctions of Advanced Automotive Sheet Steel by Using Different Electrode Pressures

Abstract: Based on this study, the effects of the different types of welding currents and electrode pressures on the tensile shear properties of the resistance spot welding (RSW) which are the joints of the commercial DP600 sheet steel are now been investigated. In addition to the fact that the electrode pressure is not much of a popular piece or topic of discussion in the literature, the expression of the mechanical properties of these commercial materials (most importantly in the DP and in the high strength steels). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
0
4
0
1
Order By: Relevance
“…Heat treatment processes can be used to modify the surface and structural properties of low carbon steel in order to have a hard outer surface and a ductile and tough inner core, which is beneficial for engineering applications such as cams, gears, and shafts. These properties assist the resistance in wear and shock, thus extending the life of the component [1][2][3]. Carburizing is an ancient thermo-chemical heat treatment used to harden the surface of low carbon steel by diffusing carbon into it.…”
Section: Introductionmentioning
confidence: 99%
“…Heat treatment processes can be used to modify the surface and structural properties of low carbon steel in order to have a hard outer surface and a ductile and tough inner core, which is beneficial for engineering applications such as cams, gears, and shafts. These properties assist the resistance in wear and shock, thus extending the life of the component [1][2][3]. Carburizing is an ancient thermo-chemical heat treatment used to harden the surface of low carbon steel by diffusing carbon into it.…”
Section: Introductionmentioning
confidence: 99%
“…This can cause micro-void formation (Figure 4(a)). 35,46,47 EDS analysis was carried out to examine if there were differences in the chemical composition of RSW specimens. Supplementary Figure 11 indicates SEM micrographs taken from specimens that were welded by using 8 kA-1.96 kN and 12 kA-2.94 kN welding parameters, and Supplementary Table 7 indicates EDS results.…”
Section: Metallurgical Characteristicsmentioning
confidence: 99%
“…In [18], weld current was the major governing factor affecting the tensile shear strength of resistance spot welded specimens in dissimilar joints formed by stainless steel 304 and galvanized steel, as it presented a high percentage compared to welding time and force. In [19][20], it was shown that using a high welding current, the material can exhibit high mechanical properties, and the tensile shear load-bearing capacity increased as the welding current increased.…”
Section: Introductionmentioning
confidence: 99%